judul jurnal Pemilihan Lokasi Awal Usaha Bagi Usaha Mikro Kecil Dan Menengah Dengan Metode Analitycal Hierarchy Process: Selection of Initial Business Locations for Micro, Small and Medium Enterprises Using the Analytical Hierarchy Process Method - Ida bagus Komang Krizena Adhiarta; Wina Witanti; Puspita Nurul Sabrina (Journal of Information Technology, 2021)
Micro, Small and Medium Enterprises (MSMEs) are independent productive economies carried out by individuals or business entities. The problem that arises is that prospective MSME actors have their own criteria regarding the ideal location according to the desired criteria so that the chosen location will determine and produce various possibilities. To be able to solve this problem, this study proposes the use of the AHP method as a multi-criteria calculation medium in order to produce various possible locations for the perspective of potential perpetrators. The criteria used in this study include the environment, accessibility, and facilities. In addition, Geographic Information System (GIS) technology is also used in this study as a recommendation for visualization media produced by Analitycal Hierarchy Process (AHP) and the process of collecting population data in West Bandung Regency. Based on the integration of GIS and AHP carried out in this study, it is concluded that the calculation with the highest weight is environment with a value of 0.633. Next is accessibility with 0.26 and the last is facilities with a value of 0.106. As for the location, Padalarang sub-district is a suitable location to be used as a MSME location because it has the highest score of 3,291. The results of these calculations are obtained from inputting the weight of the criteria that produce normalization and the results will be multiplied by the value of the existing alternatives.